Emotional Challenges and Coping Mechanisms of Temporary Faculty in a Philippine State College - Ramiso, Dennis C. (Future Science / FSH-PH Publications, 2025)
This study explores the emotional challenges and coping strategies of temporary permanent faculty members in a state college in the Bicol Region, whose positions were opened for public application, placing them in a state of employment precarity. Anchored on Lazarus and Folkman’s Transactional Model of Stress and Coping, this qualitative case study aims to provide an in-depth understanding of how faculty members perceive, experience, and respond to job-related uncertainty. Five faculty members from diverse disciplines—Social Studies, Science, Mathematics, Electrical Technology, and Agriculture—participated in semi-structured, one-on-one interviews. Through thematic analysis, key emotional responses were identified, including persistent anxiety, diminished self-worth, professional disillusionment, and fear of displacement. The analysis also revealed coping mechanisms rooted in relational, cognitive, and spiritual domains, such as leaning on familial and peer support, engaging in religious reflection, and reframing negative experiences with professional optimism. These findings illuminate how employment insecurity not only disrupts professional stability but also deeply impacts faculty well-being and institutional trust. The study suggests the urgent need for transparent and supportive communication protocols in higher education institutions to buffer the psychosocial toll of employment transitions.